2019
DOI: 10.1111/ctr.13570
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of percutaneous transhepatic biliary drainage for biliary strictures following pediatric liver transplantation

Abstract: Background We present a retrospective analysis of our experience with pediatric liver transplantation (LT), focusing on the long‐term outcome of percutaneous transhepatic biliary drainage (PTBD) for post‐transplant biliary strictures. Methods Fifty‐three PTBDs were performed for 41 pediatric recipients with biliary strictures. The median ages at LT and PTBD were 1.4 and 4.4 years, respectively. The median observation period was 10.6 years. Results Post‐transplant biliary strictures comprised anastomotic strict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Single‐center reports of biliary stricture management have stated high success rates—all with variable approaches and time intervals between procedures, highlighting the inability for the literature to support a single approach. ( 3,12‐14 ) In this study, the intervals were longer with ERCP than with PTC. Single‐center studies have also reported longer time intervals between ERCP procedures, ranging between 2 and 3 months, ( 10,15 ) while studies employing PTC have reported shorter time intervals.…”
Section: Discussionmentioning
confidence: 53%
“…Single‐center reports of biliary stricture management have stated high success rates—all with variable approaches and time intervals between procedures, highlighting the inability for the literature to support a single approach. ( 3,12‐14 ) In this study, the intervals were longer with ERCP than with PTC. Single‐center studies have also reported longer time intervals between ERCP procedures, ranging between 2 and 3 months, ( 10,15 ) while studies employing PTC have reported shorter time intervals.…”
Section: Discussionmentioning
confidence: 53%
“…In the pediatric population, the existing pool of data on pediatric biliary complications is relatively small and heterogeneous. Different techniques and treatment algorithms are used at different centers, and encompass endoscopic, percutaneous, and surgical routes and are also likely subject to variability in their transplant populations 6,10,11,14–16,26,31,33,35–38,41–66 . A brief summary of the existing literature regarding the outcomes of pediatric patients who underwent non‐surgical biliary complication management after liver transplant is provided in Table 6.…”
Section: Discussionmentioning
confidence: 99%
“…The group with the standardized protocol had a success rate of 80% with a median drain dwell time of 49 days, while the second group with the non‐standard balloon dilation intervals had a success rate of 61.1% and a drain dwell time of 89 days 61 . A series of studies published by the Transplant Surgery group at Jichi Medical University, from 2018 to 2019 assessed the outcomes of biliary complications in their pediatric transplant population 37,64,65 . In one of the publications, 44 patients with biliary anastomotic strictures were managed with either PTBD or double‐balloon enteroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Overall technical success of percutaneous biliary drainage ranges from 88% with most series reporting 100% success. 12…”
Section: Techniques Of Percutaneous Transhepatic Cholangiography Post-liver Transplantmentioning
confidence: 99%
“…Sanada et al reported a failure rate of 18.8% (9/48) with failures requiring rendezvous procedures with endoscopy, surgical reanastomosis, or retransplantation. 12 At our institution, 73 cases of transplant-related biliary stenosis were managed percutaneously with long-term successful outcome after a single procedure in 48% (n ¼ 35). The remainder 64% (n ¼ 47) of the patients had recurrences requiring repeat PTC and cholangioplasty with some eventually leading to surgical revision or retransplantation.…”
Section: Maintenance Of Biliary Drain and Stricturesmentioning
confidence: 99%